The better distant phosphor configurations for enhancing WLED color intensity: YVO4:Eu3+ and YF3:Mn2+ - Ha Thanh Tung; Huu Phuc Dang (Universitas Ahmad Dahlan, 2023)
The distant phosphor configuration produces more illuminating beams than the two settings containing conformal or in-cup phosphor. When this configuration is used, though, it is difficult to manage the color standard of light-emitting diodes (LEDs). As a result, in past few years, numerous studies have focused on controlling the color standard of distant phosphor configurations. Until present, two distant phosphor configurations of single- and triple-film phosphor configurations, have been used to improve color standards. This research will investigate the ideal configuration among these configurations in terms of color rendering index (CRI), color quality scale (CQS), lumen output (LO), as well as color homogeneity for multi-chip white LEDs (WLEDs). WLEDs, operating at five different temperatures of color between 5600 K and 8500 K, are used to perform the studies. The results reveal that the three-sheet phosphor setting would be more desirable, with greater CRI, CQS, and lumen efficiency (LE) indexes. Furthermore, when using a triple-layer phosphor arrangement, color variation is reduced, resulting in a rise in color consistency. This conclusion is possibly verified by using Mie theory to analyze scattering properties in distant phosphor setup, making the study findings legitimate and important data to produce more advanced WLEDs.